Hypertension and exercise: the basis for prescription - Marques, José Pedro (2015)
Physical activity is associated with health benefits including a reduction in blood pressure (BP). A recent meta-analysis shows that exercise may reduce BP to a degree comparable to first-line BP-lowering drugs. It was originally thought that the BP-lowering effect of exercise was limited to endurance exercise and that resistance or isometric exercise was harmful. Recent evidence contests this idea. The evidence is scarce but suggests a role for exercise in the primary prevention of hypertensive disease. The favourable influence of exercise on important risk factors such as hypertriglyceridemia and overweight has already been demonstrated. Exercise is important in the primary and secondary prevention of hypertension. For most patients, the benefits of exercise largely exceed the risks. For individuals at risk, medical evaluation is indicated in order to allow safe and patient-oriented prescription of exercise.